2020
DOI: 10.1001/jamanetworkopen.2019.21669
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertrophic Obstructive Cardiomyopathy With Outcomes Following Transcatheter Aortic Valve Replacement

Abstract: Author Contributions: Drs Bandyopadhyay and Kalra had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Drs Bandyopadhyay, Chakraborty, Naidu, and Kalra contributed equally to the concept and design of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…7 Conversely, another study showed that TAVR in patient with concomitant HCM was associated with substantially worse in-hospital outcomes, including cardiogenic shock, renal failure, and death. 8 Overall, the presentation of severely obstructive HOCM and significant aortic stenosis is not uncommon, and that patients can undergo a combined surgical myectomy and AV replacement successfully along with optimal medical therapy as reported in our case.…”
Section: Discussionsupporting
confidence: 59%
“…7 Conversely, another study showed that TAVR in patient with concomitant HCM was associated with substantially worse in-hospital outcomes, including cardiogenic shock, renal failure, and death. 8 Overall, the presentation of severely obstructive HOCM and significant aortic stenosis is not uncommon, and that patients can undergo a combined surgical myectomy and AV replacement successfully along with optimal medical therapy as reported in our case.…”
Section: Discussionsupporting
confidence: 59%
“…In patients with significant LVOT obstruction, some degree of AS may be protective due to an increase in afterload. However, when the patient's AS progresses to the point of needing treatment, relief of the aortic valve obstruction with valve replacement leads to an immediate dramatic decrease in afterload and can acutely worsen LVOT obstruction with the potential for severe hemodynamic instability and a “suicide ventricle.” 7 While often these patients remain stable, the presence of hypertrophic cardiomyopathy with LVOT obstruction in patients undergoing TAVR has been shown to confer an increased incidence of postoperative cardiogenic shock (16.28 vs. 3.43%, p < .001) as well as increased in‐hospital mortality (18.6 vs. 2.91%, p < .001) 14 …”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated that concomitant HOCM was associated with substantially worse in-hospital outcomes, including cardiogenic shock, renal failure, and death, in patients undergoing TAVI. 4) There is a management dilemma in patients with AS and coexisting HOCM undergoing TAVI. TAVI for AS complicated with HOCM would introduce hemodynamic collapse due to deteriorated LVOTO caused by the abrupt afterload decrease.…”
Section: Discussionmentioning
confidence: 99%